Development of HOTS-Based Student Worksheets on Trigonometry material in Improving Problem Solving Ability - Nurul Hidayah; Dewi Asmarani; Maryono Maryono (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
One of the impacts of the Covid 19 pandemic is that learning is carried out online so that applications have sprung up to help students solve math problems, as a result students' problem-solving skills are reduced. In addition, the Student Worksheets that has been used so far only contains routine questions, not HOTS questions. For this reason, it is necessary to develop HOTS-based worksheets to improve problem solving abilities. The purpose of this study was to describe the process of developing valid, practical and effective HOTS-based worksheets on Trigonometry material in improving problem solving skills for class X SMKN 3 Boyolangu Tulungagung. This research is research and development called Research and Development (R&D) with the ADDIE development model which includes analysis, design, development, implementation, and evaluation. Sampling used purposive sampling method and the 2 classes selected were Class X Electronics Engineering 4 as the experimental class and Class X Automotive Engineering 4 as the control class. Based on the results of the validator, the responses of educators and students, the results of the research in the form of HOTS-based worksheets on Trigonometry for class X developed using the ADDIE development model were declared valid, practical, effective in improving problem solving skills.